3D Stacked Chips From Emerging Processes to Heterogeneous Systems - Elfadel, Ibrahim (Abe) M.; Fettweis, Gerhard (Springer International Publishing : Imprint: Springer, 2016)
This book explains for readers how 3D chip stacks promise to increase the level of on-chip integration, and to design new heterogeneous semiconductor devices that combine chips of different integration technologies (incl. sensors) in a single package of the smallest possible size.  The authors focus on heterogeneous 3D integration, addressing some of the most important challenges in this emerging technology, including contactless, optics-based, and carbon-nanotube-based 3D integration, as well as signal-integrity and thermal management issues in copper-based 3D integration. Coverage also includes the 3D heterogeneous integration of power sources, photonic devices, and non-volatile memories based on new materials systems.   •Provides single-source reference to the latest research in 3D optoelectronic integration: process, devices, and systems; •Explains the use of wireless 3D integration to improve 3D IC reliability and yield; •Describes techniques for monitoring and mitigating thermal behavior in 3D ICs; •Includes discussion of 3D integration of high-density power sources and novel NVM.